The Readiness of Learning Object Materials during the COVID-19 Pandemic - Emilya Ully Artha; Andi Widiyanto; Nugroho Agung Prabowo (Bina Nusantara University, 2021)
The current COVID-19 pandemic requires everyone to limit their activities outside home. This situation also affects the learning process, which requires students and teachers to do their work from home without having to meet face to face following the government policies in schools. Therefore, they must use electronic learning (e-learning) to solve these problems. However, this e-learning model has not been well responded by teachers for learning activities. The research examines the readiness of Learning Object Materials (LOM) during the pandemic at two vocational schools in Magelang. To assess the teachers’ readiness, a mixed-method is used, namely qualitative and quantitative methods. Interview and technical assistance are also done in the research. The results show how the material can be completed using the available time so that the teachers can focus on deepening the material and increasing correspondence. The use of free software using a computer can answer the e-learning model. Moreover, after mentoring, there is a 27% increase in understanding about LOM materials. However, it is also found that teachers are not ready and do not understand how to start online learning and use elearning. There are problems in knowledge, the Internet, the LOM process, facilities and infrastructures, as well as the combination of theory and practice.